Area under the curves, can you make a right choice?

Calculus Level 2

Take a point A A on the graph of y = f ( x ) , y=f(x), and let B B be a point on the graph of y = x y=\sqrt{x} such that A B AB is parallel to the y y -axis. Call the area bounded by these two curves and the segment A B AB as R . R.

Now, let C C be a point on the y y -axis such that A C AC is parallel to the x x -axis. Call the area bounded by the curve y = f ( x ) , y=f(x), the y y -axis, and the segment A C AC as S . S.

Given that the function f f is continuous and the areas R R and S S are equal, which of the following statements is true?

There is no such function f f There is only one such function f f There are more than one but finitely many such functions f f There are infinitely many such functions f f

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

6 solutions

Tom Engelsman
Mar 4, 2018

Let us define the regions R = 0 x 0 f ( x ) x d x R = \int_{0}^{x_0} f(x) - \sqrt{x} dx and S = 0 x 0 f ( x 0 ) f ( x ) d x S = \int_{0}^{x_0} f(x_0) - f(x) dx about the point x = x 0 . x = x_0. If R = S R = S area-wise, then we obtain:

0 x 0 f ( x ) x d x = 0 x 0 f ( x 0 ) f ( x ) d x 2 0 x 0 f ( x ) d x = x 0 f ( x 0 ) + 0 x 0 x d x \int_{0}^{x_0} f(x) - \sqrt{x} dx = \int_{0}^{x_0} f(x_0) - f(x) dx \Rightarrow \boxed{ 2\int_{0}^{x_0} f(x) dx = x_0 \cdot f(x_0) + \int_{0}^{x_0} \sqrt{x} dx} (i)

If we now differentiate both sides of (i) with respect to x 0 x_0 , we next obtain a first-order ODE:

2 f ( x 0 ) = f ( x 0 ) + x 0 f ( x 0 ) + x 0 f ( x 0 ) 1 x 0 f ( x 0 ) = 1 x 0 2f(x_0) = f(x_0) + x_0 f'(x_0) + \sqrt{x_0} \Rightarrow \boxed{ f'(x_0) - \frac{1}{x_0} \cdot f(x_0) = -\frac{1}{\sqrt{x_0}}} (ii)

Multiplying (ii) through by the integrating factor 1 x 0 \frac{1}{x_0} now yields:

( f ( x 0 ) x 0 ) = 1 x 0 3 / 2 f ( x 0 ) x 0 = 2 x 0 + C f ( x 0 ) = 2 x 0 + C x 0 (\frac{f(x_0)}{x_0})' = -\frac{1}{x_0^{3/2}} \Rightarrow \frac{f(x_0)}{x_0} = \frac{2}{\sqrt{x_0}} + C \Rightarrow \boxed{ f(x_0) = 2\sqrt{x_0} + C \cdot x_0} (iii)

Hence, there is an infinite number of functions f ( x ) f(x) that satisfy the above area condition.

Multiplying (ii) through by the integrating factor now yields.... ? Huh?

John Carpenter - 3 years, 2 months ago

Log in to reply

If you look closely, grouping the left side of (ii) in one fraction results in almost the quotient rule of derivation. Thus, multiplying by the integrating factor means you would be adding the missing part needed for the reversion of the quotient rule (for the integration, so the name).

Renato Battistin - 3 years, 2 months ago

Log in to reply

Holy Toledo, never would have seen that

John Carpenter - 3 years, 2 months ago

Log in to reply

@John Carpenter It's a standard technique in solving differential equations that everyone learns in class, Search it up, it's a famous technique literally called solving differential equations by integrating factors.

David Weisberg - 3 years, 2 months ago

But the function should also satisfy f(0) =0 which you have taken up during solving the equation. Hence we will get a definite value of 'C' Which contradict with your result..

Shivpreet Sharma - 3 years, 1 month ago
Chan Lye Lee
Mar 3, 2018

Partial solution:

Note that f ( x ) = 2 x + k x f(x)=2\sqrt{x}+kx , where k 0 k\ge 0 , are solutions.

From the figure one can immediately deduce: x A = x B x_A=x_B and y A = y C y_A=y_C .

Express R R and S S via integrals:

R = 0 x A ( f ( x ) x ) d x R = \int_0^{x_A} (f(x) - \sqrt{x}) dx

S = x A y A 0 x A f ( x ) d x S = x_A y_A - \int_0^{x_A} f(x) dx

R = S 0 x A f ( x ) d x 0 x A x d x 2 3 x A 3 2 = x A y A 0 x A f ( x ) d x R = S \quad \Leftrightarrow \quad \int_0^{x_A} f(x) dx - \underbrace{\int_0^{x_A} \sqrt{x} dx}_{\frac{2}{3} x_A^{\frac{3}{2}}} = x_A y_A - \int_0^{x_A} f(x) dx

0 x A f ( x ) d x = 1 3 x A 3 2 + 1 2 x A y A \Leftrightarrow \quad \boxed{\int_0^{x_A} f(x) dx = \frac{1}{3} x_A^{\frac{3}{2}} + \frac{1}{2} x_A y_A} , i.e. F ( 0 ) = 0 F(0)=0

Find a singular f f to solve the equation:

e.g. f ( x ) = 1 2 x + 1 2 y A f(x) = \frac{1}{2} \sqrt{x} + \frac{1}{2} y_A

F ( x ) = 1 3 x 3 2 + 1 2 x y A \Rightarrow F(x) = \frac{1}{3} x^{\frac{3}{2}} + \frac{1}{2} x y_A , which satisfies F ( 0 ) = 0 F(0)=0 .

To obtain infinitely many solutions, add a paramterized term to F ( x ) F(x) such that it doesn't change the value of 0 x A f ( x ) d x \int_0^{x_A} f(x) dx :

F n ( x ) = 1 3 x 3 2 + 1 2 x y A + sin ( 2 π x A x ± n π ) F_n(x) = \frac{1}{3} x^{\frac{3}{2}} + \frac{1}{2} x y_A + \sin\left(\frac{2 \pi}{x_A} x \pm n \pi \right)

f n ( x ) = 1 2 x + 1 2 y A + 2 π x A cos ( 2 π x A x ± n π ) \Rightarrow \boxed{f_n(x) = \frac{1}{2} \sqrt{x} + \frac{1}{2} y_A + \frac{2 \pi}{x_A} \cos\left(\frac{2 \pi}{x_A} x \pm n \pi \right)} .

It can easily be seen that:

0 x A f n ( x ) d x = [ 1 3 x 3 2 + 1 2 x y A + sin ( 2 π x A x ± n π ) ] 0 x A = 1 3 x A 3 2 + 1 2 x A y A + sin ( ( 2 + n ) π ) 0 sin ( n π ) 0 = 1 3 x A 3 2 + 1 2 x A y A \int_0^{x_A} f_n(x) dx = \left[\frac{1}{3} x^{\frac{3}{2}} + \frac{1}{2} x y_A + \sin\left(\frac{2 \pi}{x_A} x \pm n \pi \right)\right]_0^{x_A} \\ = \frac{1}{3} x_A^{\frac{3}{2}} + \frac{1}{2} x_A y_A + \underbrace{\sin\left((2+n) \pi \right)}_{0} - \underbrace{\sin\left( n \pi \right)}_{0} \\ = \frac{1}{3} x_A^{\frac{3}{2}} + \frac{1}{2} x_A y_A

which proves that infinitely many f ( x ) f(x) exist for this problem set.

Maxence Seymat
Mar 13, 2018

First, x 0 , 0 x f ( x ) f ( t ) d t = 0 x f ( t ) t d t \forall x\geq 0, \int_0^x f(x)-f(t) dt = \int_0^x f(t)-\sqrt{t}dt thus x > 0 , f ( x ) = f ( x ) / x + g ( x ) \forall x>0, f'(x)=f(x)/x + g(x) where g g is partially contiguous. Using Cauchy linear theorem there is a real vector family of such f functions. Moreover, f 0 f\neq 0 because g ( 1 ) 0 g(1)\neq 0 . There are infinitely many such f functions.

Amar Vijay
Mar 16, 2018

When the two Areas R and S are evaluated and equated it's found that the expression doesn't contain f (x) which implies that out can be anything.

Ariijit Dey
Mar 15, 2018

Alternatively you can compute the integral 0 B ( f x ) d x \int_{0}^{\sqrt{B}} (f-\sqrt{x})dx and set this equal to B C 0 B ( f . d x ) BC-\int_{0}^{B} (f.dx) where B is the extreme x co-ordinate (on right) now R = S R=S gives 2. 0 B ( f . d x ) = B C + 0 B ( x d x ) = B C + 2 3 B 3 2 2.\int_{0}^{B} (f.dx)=BC+\int_{0}^{B} (\sqrt{x}dx)=BC+\frac{2}{3}B^{\frac{3}{2}} Also note that this implies 0 B ( f x ) . d x = 1 3 B 3 2 \int_{0}^{B} (f-x).dx=\frac{1}{3}B^{\frac{3}{2}} the later implies, 0 B ( f . d x ) = 1 3 B 3 2 + B 2 2 \int_{0}^{B} (f.dx)=\frac{1}{3}B^{\frac{3}{2}}+\frac{B^2}{2} this implies B = C B=C

Although it was not necessary to show that to have consistency B = C B=C is necessary and sufficient yet this scales down the degree of freedom in x-y directions to 1; i.e in the infinite multiset S ( n × n ) S(n \times n) we are only left with S ( n ) S(n) subset; Thus only 1 n \frac{1}{n} of the R × R R \times R contributes to our choice;

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...